2014
DOI: 10.1155/2014/215140
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40 as a Novel Factor Associated with Inflammation and Catabolic Mechanisms in Osteoarthritic Joints

Abstract: YKL-40 is associated with tissue injury and inflammation, and consequently to diseases in which these mechanisms lead to tissue degradation, for example, asthma and rheumatoid arthritis. The purpose of the present study was to investigate if YKL-40 is also a significant factor in osteoarthritis (OA) by assessing associations of YKL-40 with mediators related to the pathogenesis of OA: cartilage destructing matrix metalloproteinases (MMPs) and proinflammatory cytokines interleukin-6 (IL-6) and interleukin-17 (IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 26 publications
1
36
1
Order By: Relevance
“…The circulating levels of YKL-40 in patients with RCC detected in the present study were higher than those in healthy people or in patients with other diseases measured in our laboratory recently [13][14][15]. Increased levels of YKL-40 have been associated with diseases characterized by acute or chronic inflammation and also with cancer [4].…”
Section: Discussioncontrasting
confidence: 39%
“…The circulating levels of YKL-40 in patients with RCC detected in the present study were higher than those in healthy people or in patients with other diseases measured in our laboratory recently [13][14][15]. Increased levels of YKL-40 have been associated with diseases characterized by acute or chronic inflammation and also with cancer [4].…”
Section: Discussioncontrasting
confidence: 39%
“…A growing number of investigations have found that the recently discovered glycoprotein YKL-40 could be involved in the inflammatory joint process. YKL-40, the human chitinase 3-like-1 protein, is linked to different mediators of inflammation and cartilage damage [25]. It has been shown that YKL-40 synthesis is related to joint inflammation, tissue remodeling, and alteration of cartilage in OA joint [26].…”
Section: Discussionmentioning
confidence: 99%
“…Proinlammatory interleukins, such as IL-2, IL-6, IL-12, IL-13, IL-17, and IL-18, did not induce YKL-40 transcription in astrocytes [23], while IL-6 and IL-17 showed enhanced production in human primary chondrocyte culture [22,24].…”
Section: Ykl-40 Regulationmentioning
confidence: 93%
“…Other studies indicated that YKL-40 increased also in inlammatory disorders associated with tissue remodeling and destruction [24,49].…”
Section: Proposed Functions For Ykl-40mentioning
confidence: 99%